Respuesta :

W0lf93
The answer is -12 + 20x ≥ –6x 9. The inequality is –4(3 – 5x)≥ –6x 9. The first step is to multiply factors on the left side. The intermediary steps are: (-4)*(3) - (-4)*(5x) ≥ –6x 9. -12 - (-20x) ≥ –6x 9. So, the first step will be: -12 + 20x ≥ –6x 9.

Answer:

The correct option is 4.

Step-by-step explanation:

The given inequality is

[tex]-4(3-5x)\geq -6x+9[/tex]

Use BODMAS and solve the brackets first.

Using distributive property, the given inequality can be written as

[tex]-4(3)-4(-5x)\geq -6x+9[/tex]

[tex]-12+20x\geq -6x+9[/tex]

The first step in solving the given inequality is

[tex]-12+20x\geq -6x+9[/tex]

Therefore option 4 is correct.